How Agroecological Transition Frameworks Are Reshaping Agroecology: A Review - Ana Filipa Fonseca; Fabíola Polita; Lívia Madureira (Land)
The “agroecological transition” has emerged as a framework that aims to explain the complex changes taking place in agrifood systems. This study offers a mapping of the emergence of this framework, and aims to demonstrate that the agroecological transition can refer to different perspectives beyond the simple combination of two concepts. We carried out a bibliometric analysis of 298 articles (2012–2023), searched using the command “agroecologic* transition*”. We used VOSviewer software (version 1.6.20), which is able to reveal clusters of co-citations of the most cited authors and articles. This result, in turn, indicates the existence of different perspectives on the use of agroecological transitions. Four clusters were found: (i) “Techniques and Practices”, represented by articles that document the agroecological transition as an expression of specific agricultural techniques and practices; (ii) “Transition Theory”, which employs the emerging theory and its conceptual contributions; (iii) “Transition Criteria”, which involves the use of criteria to monitor the transition; and (iv) “Political and Social”, made up of articles that explore the political and social movement dimension of agroecology. Each of these clusters, and their approaches, contribute different interpretations of agroecology itself, indicating the emergence of a new framework capable of attributing new meanings to it.